Finance, Investment and Growth: Evidence for Italy. (16th July 2017) - Capolupo, Rosa
Abstract : This paper investigates the finance–growth nexus in Italy over a period of more than forty years (1965–2009). After a review of the theoretical and empirical literature, the paper provides evidence that the aggregate indicators of financial depth, constructed by Beck et al. (2000a ) and widely used in the literature, played no significant role in spurring economic growth, after controlling for the main determinants of growth and corrected for endogeneity biases. The indicator of private credit to GDP—considered the most important measure of financial development—adversely affected growth in the period studied. By contrast, financial development indicators have a positive impact when are associated directly with the real investment rate. The results are robust to the inclusion of various controls and changes in the conditioning set.